An Empirical Study of the Impact of Metro Station Proximity on Property Value in The Case of Nanjing, China - Zhang, Xinyue; Jiang, Yanqing (Asian Development Policy Review, 2014)
This paper analyzes the impact of metro station proximity on property value from both theoretical and empirical perspectives. Data on second-hand apartments within six kilometers of metro line 1 and 2 stations in Nanjing are used. Our empirical results show that metro station proximity has a positive partial effect on property value. The degree of impact diminishes with the increase of the distance. The extent of impact reaches the largest when the distance is less than five hundred meters, and is still remarkable when the distance is within two kilometers. The effect becomes insignificant when the distance is larger than two kilometers. Our empirical results also show that with the distance increasing, the extent of price variation is widened first, reaching a peak when the property is within one kilometer, and then decreases. In addition, metro station proximity in suburban areas is shown to have a higher positive impact on property value compared with metro station proximity in urban areas.